Hydrodeoxygenation of microalgae oil to green diesel over Pt, Rh and presulfided NiMo catalysts. Issue 5 (12th October 2015) - Zhou, Lin; Lawal, Adeniyi
Abstract : The catalytic characteristics, activity and selectivity of 1% Pt/Al2 O3, 0.5% Rh/Al2 O3 and presulfided NiMo/Al2 O3 catalysts have been investigated in the hydrodeoxygenation of microalgae ( Nannochloropsis salina ) oil to produce green diesel in a microreactor. Abstract : The catalytic characteristics, activity and selectivity of 1% Pt/Al2 O3, 0.5% Rh/Al2 O3 and presulfided NiMo/Al2 O3 catalysts have been investigated in the hydrodeoxygenation of microalgae ( Nannochloropsis salina ) oil to produce green diesel in a microreactor. Coke accumulation decreased in the order NiMo > Pt > Rh. The amount of formed coke over NiMo increased with reaction duration, while no on-stream time dependence was found over Pt and Rh. Rhodium was found to be very active for CH4 production via hydrocracking at its freshly reduced state. The activity and selectivity of all three investigated catalysts were positively affected by increased reaction pressure, temperature, H2 /oil ratio and residence time. The selectivity of NiMo for the hydrodehydration (DHYD) route was changed to a hydrodecarbonylation/hydrodecarboxylation (DCO/DCO2) route at a reduced H2 /oil ratio and residence time, while the selectivity of Pt and Rh for the DCO/DCO2 route was not affected by the reaction conditions. The highest hydrocarbon yield, 76.5%, was obtained over 1% Pt (310 °C, 500 psig, 1000 SmL mL −1 gas/oil ratio, 1.5 s residence time), which is 13.8% higher than that over NiMo (360 °C, 500 psig, 1000 SmL mL −1 gas/oil ratio, 1 s residence time). The 50 °C decrease in the reaction temperature for Pt indicates possible energy saving via heat supply.